Faktor Risiko Stunting Pada Anak Usia Di Bawah Tiga tahun - Maria Sambriong; Yulianti K. Banhae; Emilia E. Akoit; Yohanes M. Abanit (Bima Nursing Journal, 2023)
The problem of stunting must be resolved immediately because it will have an impact on Indonesia's human resources in the future. Indonesia's stunting rate still exceeds WHO recommendations in 2018. Starting around 2013, the East Nusa Tenggara Region recorded the highest stunting rate in Indonesia. Stunting has the potential to harm the country by 2% and 3% of GDP each year. Based on GDP, losses could reach IDR 474.9 trillion in 2019. The purpose of this study was to find out what factors are most likely to cause stunting in children under the age of three. An observational study using a case-control design. There were 107 children in the population, and simple random sampling was used to select at least 74 of them. Mothers with children aged 6 to 3 years who are stunted or not a respondent. The chi-square test and relapse counting were used in the investigation. The study found that sex (p = 0.020), exclusive breastfeeding (p = 0.006), low birth weight (0.000), and parenting (0.033) were four gambling factors associated with inhibition. Confounding was caused by the mother's height (p=0.050). The most common risk factor for stunting is LBW which has an OddssRatio of 11.189. This shows that where children born with low weight have an eleven times higher risk of experiencing stunting compared to children born with normal weight. Concluded that risk factors associated with stunting are sex, LBW, exclusive breastfeeding, and parenting. Noted that LBW's most dominant variable related to stunning.